TRANSFORMASI PARADIGMA PEMIDANAAN DALAM KUHP NASIONAL ANTARA KEADILAN RESTORATIF DAN TANTANGAN IMPLEMENTASI LIVING LAW - Luthfi, Amir; Novi Maimory, Aminoel Akbar; Miswar, Miswar (Jurnal Pahlawan, 2026)
The implementation of the New Criminal Code (Law No. 1 of 2023) as of January 2, 2026, marks the decolonization of Indonesia’s criminal law system, shifting from a retributive paradigm toward restorative, corrective, and rehabilitative justice. This normative juridical research examines the dualism between the principle of legality and the recognition of living law, alongside law enforcement challenges concerning Artificial Intelligence (AI)-based crimes. The findings reveal three key issues: (1) potential legal uncertainty arising from living law lacking rigid parameters; (2) the necessity for an ideological reorientation among law enforcement officers regarding the application of alternative sanctions; and (3) a legal vacuum concerning the criminal liability of AI entities. It concludes that the 2023 Criminal Code requires precise derivative regulations. This article recommends standardizing customary law criteria to prevent over-criminalization, as well as strengthening the oversight of judicial pardon discretion to avoid sentencing disparities. Keywords : 2023 Criminal Code, Legal Decolonization, Living Law, Restorative Justice, Artificial Intelligence, Principle of Legality